Deep incarnation: God's redemptive suffering with creatures - Edwards, Denis (Duffy lectures in global Christianity, 2019)
Deep incarnation in recent theology -- Irenaeus and the earthly incarnation of the Word -- Athanasius on the depths of the incarnation -- Karl Rahner on incarnation in an evolutionary world -- The cross: sacrament of God's redemptive suffering with creatures.